Analysis of local habitat selection and large-scale attraction/avoidance based on animal tracking data: is there a single best method? - Mercker, Moritz; Schwemmer, Philipp; Peschko, Verena; Enners, Leonie; Garthe, Stefan (Movement Ecology, 2021)
New wildlife telemetry and tracking technologies have become available in the last decade, leading to a large increase in the volume and resolution of animal tracking data. These technical developments have been accompanied by various statistical tools aimed at analysing the data obtained by these methods.